THE IMPLEMENTATION OF LEGISLATION FUNCTION OF THE REGIONAL REPRESENTATIVE COUNCIL IN THE PREPARATION OF REGIONAL REGULATIONS OF CENTRAL SULAWESI PROVINCE OF 2019-2023 - Sylvia Ari Wahyuni (Universitas Tadulako, 2024)
The problem studied is the implementation of the legislative function of DPRD in the formation of Central Sulawesi Provincial Regulations 2019-2023 and the role of the Central Sulawesi Provincial DPRD in forming Regional Regulations that articulate public interests. Method the research used was normative legal research which was library materials or secondary data applied Conceptual Approach and Legislative Approach (Statute Approach), and then described in descriptive terms to obtain a picture that can be understood clearly and directed to answer problems studied. The research results reveals that the implementation of legislative function of the Regional People's Representative Council in preparation of Central Sulawesi Province Regional Regulations for 2019-2023 can be seen in every stage of the formation of Regional Regulations, namely stages of planning, preparation, discussion, determination and promulgation in 2019-2023, DPRD of the Central Sulawesi Province adopted 39 regional regulations consisting of 15 DPRD initiatives and 24 regional government initiatives. Role of the Board Regional People's Representatives in forming regional regulations articulating public interests is carried out through public participation by involving the community in the drafting stage of regional regulations, involving the community in the discussion of stages of draft regional regulations and involving the community in the implementation stage of regional regulations.